QUANTITATIVE AND QUALITATIVE COMPOSITION OF ORGANIC MATTER AND ITS TRANSFORMATION IN A SURFACE LAYER OF LAKE ONEGO SEDIMENTS - Natalya Belkina (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2017)
The elemental composition of the organic matter of bottom sediments was calculated in the paper. Changes of quantitative and qualitative composition of organic matter in the course of its burial into sediments were analyzed. The paper shows zoning processes of organic matter decomposition in a sedimentary column. The rate of organic matter degradation was calculated on the basis of the profile of TOC.